HUBUNGAN ANTARA MINAT, FASILITAS DAN PERSEPSI TERHADAP KEMAMPUAN MENGAJAR GURU MATEMATIKA DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII SMP SE-KECAMATAN KASIHAN - Lina Lestari; Tri Astuti Arigiyati (Universitas Sarjanawiyata Tamansiswa, 2016)
The descriptive objectives of this research are (1) determine the trend of interesting in learning, facilities, students perception to teachers ability and mathematics achievement, (2) determine the correlation between interesting in learning, facilities, students perception to teachers ability and mathematics achievement from all variables also each variable. This is ex post facto research. The population are the seven grade of Junior High School student in Kasihan Bantul. The sample are taken with cluster random sampling. The data are obtained through test and questionnaire. The requirements analysis are normality tes, linierity tes and multikolinierity tes. The analysis of data used multiple regression analysis to determine the correlation for all variables and partial correlation analysis to determine the correlation for each variable. The result showed that the trend of interesting in learning, facilities, students perception to teachers ability is very high category and mathematics achievement high category. The result show that the value of R = 0,498, R2 = 0,248 with Fobserve = 13,068 and sign = 0,000 < 0,05, means there is a possitive and significant correlation between interesting in learning, facilities, students perception to teachers ability and mathematics achievement.